The use of the micronutrient drug «Avatar» for growing barley in the field of crop rotation - Тищенко, М. В.; Мороз, О. В.; Смірних, В. М.; Новоселецький, І. Г.; Кусков, О. Г.; Філоненко, С. В.; Ляшенко, В. В. (Scientific Progress & Innovations, 2018)
In the zone of insufficient humidification, characterized by a sharp lack of atmospheric precipitation and soil moisture, the use of the micronutrient drug «Avatar» for the cultivation of various crops remains open, relevant and requires more systematic study. The purpose of the research was to determine the effect of using the micronutrient drug «Avatar», which was used for the treatment of spring barley seeds and during vegetation of crops, on the spread of barley diseases and grain yield. Field studies were conducted in the production experiment of the Veselopodil experimental and breeding station at the Institute of Bioenergetic Cultures and Sugar Beet at the National Academy of Agrarian Sciences of Ukraine (Semenivka district, Poltava region) during 2017 in long-term field crop rotation. As a result of field studies, it was found that in the zone of insufficient humidification in the conditions of the South-Eastern Forest-Steppe of Ukraine in field crop rotation, the use of the microelement preparation «Avatar» for two-fold extra-root feeding of spring barley plants during vegetation, even under unfavorable agro-meteorological conditions (elevated temperature regime, absence a sufficient amount of precipitation), contributed to the yield of grain yield of the studied crop in the range of 4.26–4.84 t/ha. The treatment of seeds by Avicenna (0.4 l/ton) and the microelement drug «Avatar» (300 ml/t) + two spraying plants during the «Avatar» (200 ml/ha) growth provided the lowest intensity of helminthosporia strain spotting on barley plants bright – 10.5 %, which is due to the best development of plants of the studied culture and their greatest resistance to the disease.